Caso de estudio: IOI’S global challenge: moving up the palm oil value chain - Balbin Quispe, Christian (2019)
In the present case to be developed, we are introduced to IOI Corporation Behard, a leading company in the production and marketing of “Refined Palm Oil” with Tariff Item: 15.11.00, a family business that was created with a B2B sales approach and is looking for identify what actions to take to consolidate its growth by 2025. IOI began its development in the regions of Malaysia and Indonesia under a comprehensive strategy in its supply chain: upstream and downstrem; Consequently and with the support of sustainable growth, it chose to expand to the international market through procurement strategies and Joint Ventures with specialized companies and experience with products based on chemical oils, vegetable fats and oil, consolidating itself as a mini-multinational . In this way, based on the information collected and compared, identified strategies, applied theoretical bases and research methodology, a certain group of actions were identified in commercial, customs logistics, marketing, strategic planning and finance fields that IOI should consider in order to position itself with its new and current products to potential customers identified in countries such as China, Vietnam and the Netherlands, improving their competitive advantage over potential competitors in order to overcome the setbacks of import quotas, sanctions by NGOs and instability of the commodity price.